Mathematics and development of professional competencies - Saldauskienė, Jovita; Virkutis, Vytautas (Lietuvos matematikos rinkinys, 2003)
This work contains the material about forms and contents of teaching of mathematics. It contains clear description of the aims, terms, techniques and methods of teaching as well as aspects of development of students’ professional competencies. There were made the following conclusion. Mathematics teaching module in college in higher education is expedient to use emphasizing on practically applied subject. The module has to meet the specific professional competencies of student’s specialty.